The Influence of The Campus Environment on Student Learning Motivation in The Management Study Program at Nias Raya University - Derna Santi Duha; Alfianis Putri Mandasari Telaumbanua; Alfred Sarumaha; Rafael Laia; Maria Clarita Manao; Deforsi Hasiholan Gulo (HARAMAIN: Jurnal Manajemen Bisnis, 2026)
This study aims to analyze the influence of the campus environment on students’ learning motivation in the Management Study Program at Nias Raya University. The research employed a quantitative approach with a causal research design. The population consisted of students from the Management Study Program at Nias Raya University, with a sample of 30 respondents selected using purposive sampling. Data were collected through questionnaires and analyzed using SPSS version 22. The data analysis techniques included validity testing, reliability testing, classical assumption tests, simple linear regression analysis, hypothesis testing (t-test), and coefficient of determination analysis. The results indicate that all research instruments were valid and reliable. The classical assumption tests showed that the data were normally distributed, linear, and free from heteroskedasticity. The regression analysis revealed that the campus environment has a positive and significant effect on students’ learning motivation. The t-test results showed a significance value below 0.05, indicating that the research hypothesis was accepted. The coefficient of determination (R²) value of 0.315 indicates that the campus environment accounts for 31.5% of the variance in students’ learning motivation, while the remaining 68.5% is influenced by other factors not examined in this study. These findings highlight the importance of a supportive campus environment in enhancing students’ motivation to learn.